Analisis Perbandingan Kinerja Keuangan Dana Pensiun Program Pensiun Manfaat Pasti dengan Program Pensiun Iuran Pasti - , Yiyin Andryani ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The pension fund performance appraisal is based on financial statements of the pension fund. The financial statements of the pension fund net assets provide information to parties outside the pension fund. Information provided about the picture of its financial position, may also be used externally to assess the magnitude of the risks that exist on a pension fund. Generally, the pension funds consists of 2 (two) types of programs, namely Defined Benefit Pension Plan (PPMP) and Defined Contribution Pension Plan (PPIP). At the present time Defined Benefit Pension Plan (PPMP) is still dominating in the pension industry. The purpose of this study is to analyze the financial performance of the Pension Fund Defined Benefit Pension Plan (PPMP) compared to the Retirement Fund Defined Contribution Pension Plan (PPIP) for each financial ratio. The study is conducted on the pension funds in Indonesia as of December 31, 2009 that the population of it reaches 251 pension funds. This study applies a sample of 20 pension funds that come from Defined Benefit Pension Plan (PPMP) and 20 pension funds are from the Defined Contribution Pension Plan (PPIP). The Ratio which is used to examine the performance of each group is Return on Assets (ROA), Return on Investment (ROI), Cost Efficiency of Operations (EBO), Cost Efficiency Investment (EBI), Optimization of Investment Portfolio (OPI) and Fund Adequacy Ratio (RKD) in which they are all processed based on the financial statements of each fund pension. For the analysis, it applies a t test for the presence or absence of the differences in the performance of each group pension fund. The test results show that: (1) The results of t test analysis of the ROA and EBO performance data is that there is no more higher between the ROA and EBO in the pension fund Defined Benefit Pension Plan (PPMP) to the pension fund Defined Contribution Pension Plan (PPIP). It can be seen from the second count value of the significance of these data, each of which is greater than 5%. (2) The results of the analysis of the performance data to the test against ROI, EBI, and OPI in pension Defined Benefit Pension Plan (PPMP) that there is more higher than the pension fund Defined Contribution Pension Plan (PPIP). (3) The results of the analysis of the performance data to the test against RKD in pension Defined Benefit Pension Plan (PPMP) that there is more lower than to the pension fund Defined Contribution Pension Plan (PPIP). It can be seen from the significance of the ratio of the fourth count, each is smaller than 5%. As for the suggestions the government should give attention, policies, or incentives that can improve the performance of pension funds Defined Contribution Pension Plan (PPIP) if it wishes to divert participants Defined Benefit Pension Plan (PPMP) to Defined Contribution Pension Plan (PPIP).